Postoperative Pressure Ulcers After Geriatric Hip Fracture Surgery Are Predicted by Defined Preoperative Comorbidities and Postoperative Complications. Issue 8 (15th April 2020) - Galivanche, Anoop R.; Kebaish, Kareem J.; Adrados, Murillo; Ottesen, Taylor D.; Varthi, Arya G.; Rubin, Lee E.; Grauer, Jonathan N.
Abstract : Introduction: The current study sought to determine the factors predictive of postoperative pressure ulcer development by analyzing extensive multicenter outcomes data from the 2016 American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database. Methods: The 2016 NSQIP Participant Use File and Hip Fracture Procedure Targeted file were used to identify the risk factors for the development of postoperative pressure ulcers after hip fracture surgery in a geriatric cohort. Multivariate regressions were performed to identify preoperative comorbidities and postoperative complications that are risk factors for developing postoperative pressure ulcers. Results: Of 8, 871 geriatric hip fracture patients included in the study cohort, 457 (5.15%) developed pressure ulcers. Multivariate regressions identified the following preoperative risk factors for developing a postoperative pressure ulcer (in order of decreasing relative risk): preoperative sepsis, elevated platelet count, insulin-dependent diabetes, and preexisting pressure ulcer. Multivariate regressions also identified the following postoperative complications as risk factors for developing a postoperative pressure ulcer: postoperative sepsis, postoperative pneumonia, urinary tract infection, and postoperative delirium. Discussion: The identified preoperative factors and postoperative complications should help guide quality improvement programs.